1998
DOI: 10.1128/jb.180.17.4523-4531.1998
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the hrpC and hrpRS Operons of Pseudomonas syringae Pathovars Syringae, Tomato, and Glycinea and Analysis of the Ability of hrpF , hrpG , hrcC , hrpT , and hrpV Mutants To Elicit the Hypersensitive Response and Disease in Plants

Abstract: The species Pseudomonas syringae encompasses plant pathogens with differing host specificities and corresponding pathovar designations. P. syringae requires the Hrp (type III protein secretion) system, encoded by a 25-kb cluster ofhrp and hrc genes, in order to elicit the hypersensitive response (HR) in nonhosts or to be pathogenic in hosts. DNA sequence analysis of the hrpC and hrpRSoperons of P. syringae pv. syringae 61 (brown spot of beans), P. syringae pv. glycinea U1 (bacterial blight of soybeans), and P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 49 publications
(68 reference statements)
2
62
0
1
Order By: Relevance
“…'Glurk' plants, the wild-type and strains pyrC244::Tn5, pyrC244::Tn5(pCR2.1-pyrC) and pyrC244:: Tn5(pCR2.1) all caused tissue collapse typical of the hypersensitive response (HR, Fig. 4b), while the type III protein secretion system mutant hrcC118::Tn5 did not trigger an HR, as expected (Deng et al 1998). This indicated that the pyrC244::Tn5 mutant triggered typical nonhost defence responses in tobacco (Morel and Dangl 1997).…”
Section: Resultssupporting
confidence: 68%
“…'Glurk' plants, the wild-type and strains pyrC244::Tn5, pyrC244::Tn5(pCR2.1-pyrC) and pyrC244:: Tn5(pCR2.1) all caused tissue collapse typical of the hypersensitive response (HR, Fig. 4b), while the type III protein secretion system mutant hrcC118::Tn5 did not trigger an HR, as expected (Deng et al 1998). This indicated that the pyrC244::Tn5 mutant triggered typical nonhost defence responses in tobacco (Morel and Dangl 1997).…”
Section: Resultssupporting
confidence: 68%
“…Among the virulence related genes, hrp and hrc genes play an important role in pathogenicity. The hrp genes such as hrpT, hrpF and hrcC are essential for P. syringae 61 to induce the hypersensitive response in tobacco (Deng et al, 1998). Hojo et al (2008) also confirmed that hrp genes are involved in determining the pathogen's host range after analysing a mutant library of P. cichorii SPC9018.…”
Section: Discussionmentioning
confidence: 66%
“…Pseudomonas species have been classified into various pathovar groups based on their host specificity (Deng et al, 1998). Sets of hrp and hrc genes are essential and contribute to host specificity and disease development in host plants.…”
Section: Pathogenicity Island Region Of Jbc1mentioning
confidence: 99%
“…We have shown that the triggered SA and PR gene accumulation at inoculation sites is largely dependent on a TTSS. This finding, together with the fact that the type II non-host HR also requires type III secretion (Deng et al 1998), emphasizes that non-adapted bacteria build up a functional TTSS also in non-host plants and deliver effector proteins into the plant cell. The TTSS effectors subsequently might interact with cellular targets to initiate SA-associated defence responses.…”
Section: Discussionmentioning
confidence: 89%